Novel solid - phase microextraction adsorbent for the forensic detection of accelerants in arson samples [electronic resource] - 398210 Geetha Selvaraju; Umi Kalthom Ahmad, supervisor (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2007